1997
DOI: 10.1021/jo951170a
|View full text |Cite
|
Sign up to set email alerts
|

Enantiospecific Formation of Trans 1,3-Disubstituted Tetrahydro-β-carbolines by the Pictet−Spengler Reaction and Conversion of Cis Diastereomers into Their Trans Counterparts by Scission of the C-1/N-2 Bond

Abstract: The factors which effect the stereoselective formation of trans-1-alkyl-2-benzyl-3-(alkoxycarbonyl)-1,2,3,4-tetrahydro-beta-carbolines and trans-3-(alkoxycarbonyl)-1-alkyl-2-(diphenylmethyl)-1,2,3,4-tetrahydro-beta-carbolines by the Pictet-Spengler cyclization were examined by heating tryptophan derivatives with aldehydes of varied steric bulk under aprotic and acidic conditions, followed by determination of the ratio of cis to trans diastereomers so formed. The presence of a benzyl group at the N(b)-nitrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
45
0
4

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(59 citation statements)
references
References 36 publications
10
45
0
4
Order By: Relevance
“…[109] Detailed examination of the reaction conditions allowed thermodynamic trans stereocontrol by application of the N bbenzylalkyl esters of tryptophan. [108,[110][111][112] A mixture of isomers of 1,2,3-trisubstituted tetrahydro-bcarbolines was formed when small aliphatic aldehydes were used under acidic and non-acidic aprotic conditions (Table 3). Selective formation of the trans diastereomer was observed for cyclohexanecarboxaldehyde.…”
Section: Application Of Tryptophan Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…[109] Detailed examination of the reaction conditions allowed thermodynamic trans stereocontrol by application of the N bbenzylalkyl esters of tryptophan. [108,[110][111][112] A mixture of isomers of 1,2,3-trisubstituted tetrahydro-bcarbolines was formed when small aliphatic aldehydes were used under acidic and non-acidic aprotic conditions (Table 3). Selective formation of the trans diastereomer was observed for cyclohexanecarboxaldehyde.…”
Section: Application Of Tryptophan Derivativesmentioning
confidence: 99%
“…[4b, 108,111,112] The diastereomers can usually be separated by flash chromatography. The thermodynamically more-stable trans isomer could be obtained exclusively from the cis/trans mixture by epimerization of the N b -substituted cis isomer under acidic conditions (trifluoroacetic acid; Scheme 16).…”
Section: Application Of Tryptophan Derivativesmentioning
confidence: 99%
“…In fact, since 1979, Cook and co-workers studied the reaction of these compounds with aldehydes [14][15][16][17][18]. Thus, they found that the steric bulk of the carbonyl compounds, and the substituents either at the Nb nitrogen atom or at the ester group governed the diastereoselectivity of the PSR, leading preferentially to trans-1,2,3-trisubstituted tetrahydro-β-carbolines under thermodynamic stereocontrol (Scheme 3).…”
Section: Starting From Tryptophan Derivativesmentioning
confidence: 99%
“…Among the latter, many compounds are important drugs, including benzyltetrahydroisoquinoline alkaloids which are synthesized via enzymatic Pictet-Spengler reaction, i.e., condensation of aldehydes with 2-arylethanamines 58 with formation of tetrahydroisoquinolines 57 (Scheme 15). The amine component may be derivatives of phenylalkanamines [47][48][49][50][51] [52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67], amines of the naphthalene series [68], and aminoalkyl derivatives of heterocyclic compounds [69,70]. If X = O, the corresponding 1,2-oxazines, 1,2-oxazepines, and 1,2-oxazocines are obtained [71].…”
Section: Rchomentioning
confidence: 99%